(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The core aspect of this study is to explore the difficulty to produce a second language (L2) phones by Libyan Arabic learners of English. In doing so, this study adopted a quantitative design in which a quasi-experiment was used to collect the information from 4 participants from different levels and investigated the reasons behind the difficulties in producing two main segments which are the bilabial voiceless /p/ and the fricative voiced /v/as these two sounds are not found in the participants’ first language (L1). Based on the findings, it was found out that the Speech Learning Hypothesis could be applied as it claimed that the difficulties in acquiring some L2 sounds like native like is due the fact that they are similar to L1 phones, thus the Libyan Arabic learners assimilate /p/ and /v/ to their counterparts in L1 sounds which are /b/ and /f/ respectively. Interestingly, Feature Geometry could account for the outcomes of the current study as it hypothesized that L2learner is able to realize the L2 contrast, if the feature is active in an L1 then speakers of that L1 will be able to learn a contrast that relies on that feature since the feature that distinguish the English contrasts /p/ from /b/ and /f/ from /v/ is voicing and this feature is active in Libyan Arabic.